Analysis of Basic Mandarin and English Learning Needs in A Private Junior High School in Makassar - Azizah, Mirah; Samad, Ita Sarmita; S, Hasria Riski; Marsuki, Ria Riski (Universitas Negeri Semarang, 2025)
This study aims to analyze the needs for basic Mandarin and English language learning that has been conducted at a private junior high school in Makassar, as a reference for determining whether this activity should be continued and for the development of learning materials and syllabus creation. This study identifies the challenges in learning Mandarin and English after attending Mandarin and English lessons, the benefits of learning Mandarin and English, the continuity of the basic Mandarin and English training program, and the needs for learning basic Mandarin and English based on the four core language skills. This research uses a descriptive-analytical method with a quantitative approach. The data was obtained through a questionnaire distributed to 15 respondents, consisting of junior high school students from a private school in Makassar, teachers, and parents. The analysis of the questionnaire data indicates that the respondents are interested in learning Mandarin and English by increasing the number of study hours and changing the learning themes, as 53.3% of them feel they have already understood the current material well enough. In terms of Hanzi recognition and writing, they experienced significant difficulties—93.3% of the participants reported that they found learning Hanzi to be challenging. The overall results of the needs analysis for basic Mandarin and English learning suggest that students require Mandarin skills primarily to understand simple conversations and basic vocabulary.